2017
DOI: 10.1128/aac.02297-16
|View full text |Cite
|
Sign up to set email alerts
|

Nanoliposomal Buparvaquone Immunomodulates Leishmania infantum-Infected Macrophages and Is Highly Effective in a Murine Model

Abstract: Visceral leishmaniasis is a fatal parasitic neglected disease affecting 1.5 million people worldwide. Based on a drug repositioning approach, the aim of this work was to investigate the in vitro immunomodulatory potential of buparvaquone (BPQ) and to establish a safe regimen to evaluate the in vivo efficacy of BPQ entrapped by negatively charged nanoliposomes (BPQ-LP) in Leishmania infantum-infected hamsters. Small-angle X-ray scattering, dynamic light scattering, and the -potential were applied in order to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…Anti-leishmanial activity was evaluated in vitro for L. donovani, Leishmania aethiopica, L. major, Leishmania amazonensis, Leishmania mexicana, Leishmania panamensis, L. infantum, Leishmania chagasi, L. braziliensis , and L. tropica promastigotes and amastigotes resulting in IC 50 -values of 0.001–5.495 μM (Mäntylä et al, 2004a , b ; Reimão et al, 2012 ; Jamal et al, 2015 ). Animal models showed that the in vivo efficiency was higher when prodrugs of buparvaquone were applied (Croft et al, 1992 ; Garnier et al, 2007 ) or when a nanoliposomal drug preparation was used (da Costa-Silva et al, 2017 ).…”
Section: Targeting Transport Processes Of Parasites At Different Levementioning
confidence: 99%
“…Anti-leishmanial activity was evaluated in vitro for L. donovani, Leishmania aethiopica, L. major, Leishmania amazonensis, Leishmania mexicana, Leishmania panamensis, L. infantum, Leishmania chagasi, L. braziliensis , and L. tropica promastigotes and amastigotes resulting in IC 50 -values of 0.001–5.495 μM (Mäntylä et al, 2004a , b ; Reimão et al, 2012 ; Jamal et al, 2015 ). Animal models showed that the in vivo efficiency was higher when prodrugs of buparvaquone were applied (Croft et al, 1992 ; Garnier et al, 2007 ) or when a nanoliposomal drug preparation was used (da Costa-Silva et al, 2017 ).…”
Section: Targeting Transport Processes Of Parasites At Different Levementioning
confidence: 99%
“…where k B is the Boltzmann constant, T is the absolute temperature, η is the viscosity of the solvent, and D h and D app are the hydrodynamic diameter and the apparent diffusion coefficient, respectively (Costa-Silva et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The measurement for each sample was repeated for at least three times. In order to avoid multiple scattering, the samples were diluted 20-fold in the appropriate buffer before the measurements (Lamy et al, 1966; Costa-Silva et al, 2017). LP-SERT treatment was analyzed by culture microtitration as previously reported (Park and Lee, 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another drug under test for liposome delivery is buparvaquone, an extensively studied drug for the treatment of visceral leishmaniosis. da Costa-Silva et al reported that buparvaquone, which has an immunomodulatory effect in host cells, when entrapped in phosphatidylserine (PS) exposing-liposomes, as a delivery approach to macrophage, is highly effective at low doses at eliminating Leishmania infantum parasites in a hamster model ( 52 ).…”
Section: Liposomes As Carrier For Drugsmentioning
confidence: 99%